2023
DOI: 10.1101/2023.01.03.519659
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Structure of pre-miR-31 reveals an active role in Dicer processing

Abstract: As an essential post-transcriptional regulator of gene expression, microRNA (miR) levels must be strictly maintained. The biogenesis of many, but not all, miRs is mediated by trans-acting protein partners through a variety of mechanisms, including remodeling of the RNA structure. miR-31 functions as an oncogene in numerous cancers and interestingly, its biogenesis is not known to be regulated by protein binding partners. Therefore, the intrinsic structural properties of pre-miR-31 can provide a mechanism by wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 83 publications
1
10
0
Order By: Relevance
“…The DNA template for preparation of the HH-pre-miR-31-HDV was generated as previously described (30). The DNA template for preparation of the pre-miR-144, pre-miR-21, pre-let-7c, GG-pre-miR-19a and pre-miR-143 were generated by overlap-extension (OE) polymerase chain reaction (PCR) using EconoTaq PLUS 2x Master Mix (Lucigen) with primers listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The DNA template for preparation of the HH-pre-miR-31-HDV was generated as previously described (30). The DNA template for preparation of the pre-miR-144, pre-miR-21, pre-let-7c, GG-pre-miR-19a and pre-miR-143 were generated by overlap-extension (OE) polymerase chain reaction (PCR) using EconoTaq PLUS 2x Master Mix (Lucigen) with primers listed in Table S1.…”
Section: Methodsmentioning
confidence: 99%
“…Human Dicer/TRBP protein processing assays were performed as previously described with minimal modifications (30). Concentrated recombinant human Dicer/TRBP protein was diluted in 1× Dicing buffer (24 mM HEPES pH = 7.5, 100 mM NaCl, 5 mM MgCl 2 , 4 μM EDTA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…NMR studies can provide such detailed insight for nucleic acids, so far most clearly demonstrated on RNA. [17][18][19][20][21] Application to the nucleosomal DNA has so far been limited as the size (~200 kDa with histone proteins included) and the length (at least 145 bp [22] ) poses significant challenges.…”
Section: Introductionmentioning
confidence: 99%